2005
DOI: 10.1103/physrevb.71.195121
|View full text |Cite
|
Sign up to set email alerts
|

Many-body effects in the4fx-ray photoelectron spectroscopy of theU5+and

Abstract: A strictly ab initio many-electron theory was used to calculate the 4f x-ray photoelectron spectroscopy ͑XPS͒ of the free U 5+ and U 4+ ions. The calculations, based on relativistic Dirac-Fock self-consistent field ͑DF-SCF͒ and Dirac configuration interaction ͑DCI͒ wave functions ͑WF's͒, indicate that the atomic spectra have a considerable multiplet structure. However, the multiplet splitting, which is mainly manifest as a broadening of the 4f 5/2 and 4f 7/2 lines, is not as strong as for the first-row transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The I rel in Table III also show that the values for the MnO 6 levels are reduced from those for Mn 2+ by ϳ1% for J =3 to ϳ6% for J = 2 and J = 1. Thus, many-body configuration mixing, which steals intensity from the allowed configurations into higher-energy "satellites," 1,3,[14][15][16]63 is somewhat more important for the cluster than for the isolated cation. Larger configuration mixing is expected to lower the energy of the lowest states since the trace must remain invariant.…”
Section: A Mn 2p Xpsmentioning
confidence: 99%
“…The I rel in Table III also show that the values for the MnO 6 levels are reduced from those for Mn 2+ by ϳ1% for J =3 to ϳ6% for J = 2 and J = 1. Thus, many-body configuration mixing, which steals intensity from the allowed configurations into higher-energy "satellites," 1,3,[14][15][16]63 is somewhat more important for the cluster than for the isolated cation. Larger configuration mixing is expected to lower the energy of the lowest states since the trace must remain invariant.…”
Section: A Mn 2p Xpsmentioning
confidence: 99%
“…This effect has been explained and simulated by many-body theory, with the earliest work appearing in the late 1960s to 1970s [4][5][6][7][8]. Recent work [9,10] has extended the earlier treatments of transition metals to the study of free U 4+ and U 5+ cations and has shown that the U4f lines have an intrinsically complex multiplet structure that broadens the peaks and can produce prominent shoulders and doublets. Theoretical XPS simulations normally produce intensities at specific energies that are broadened to represent the effects of core-hole lifetime and instrument resolution [5,6,9,10].…”
Section: Introductionmentioning
confidence: 97%
“…The individual peaks, or multiplets, are then summed to form a composite spectrum for comparison to experiment. The theoretical U4f spectrum of the free U 5+ cation displayed doublets in both the U4f 7/2 and U4f 5/2 peaks for multiplets with FWHM = 0.9 eV [9]. In contrast, the calculated 4f spectrum of the U 4+ atom expressed less multiplet structure, where the 4f 7/2 peak had one weak shoulder and the U4f 5/2 peak had two moderate shoulders [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,50,55,56,59,60,61,62 A special attention was paid to the study of mechanisms of structure formation, which leads to widening of main peaks and appearance of extra structure in the spectra. 50,59,63 The XPS spectra of some oxides exhibit typical shake-up satellites of about ~25% intensity of the basic peaks 41,51,60,64 The calculated spectroscopic factors f Anf reflecting the fractions of the basic peak XPS intensities with the deduction of shake-up satellite intensities for the U 4f and U 5f peaks are: f U4f =0.83 and f U5f =0.86. 65,66 Shake-up satellites are located from the basic peaks toward the higher BE by ∆E sat (U4f): ~7 eV (U 4+ ); ~8 eV (U 5+ ); ~4 eV and ~10 eV (U 6+ ).…”
Section: Introductionmentioning
confidence: 99%